Answers: -2,
, -1
Step-by-step explanation:
Inverse is when the x's and y's are swapped.
g(x) = (-4, 8), (-2, 9), (4, 7), (9, -1)
g⁻¹(x) = (8, -4), (9, -2), (7, 4), (-1, 9)
g⁻¹(9) = ??? when x = 9, what is y? Answer: -2
*******************************************************************
h(x) = 3x - 4
To find the inverse, let y represent h(x). Then swap the x's and y's and solve for y:
x = 3y - 4
+4 +4
x + 4 = 3y
= y
h⁻¹(x) =
*******************************************************************
h(-1) = 3(-1) - 4
= -3 - 4
= -7
h⁻¹(h(-1)) = h⁻¹(-7)
h⁻¹(-7) =
=
= -1